Knowledge and Practice of Dysmenorrhea Self-Care Among Female Adolescents in Kathmandu - Bhele, Rajyashwaree; Chalise, Anu (NPRC Journal of Multidisciplinary Research, 2025)
Background: Dysmenorrhea, characterized by painful menstrual cramps, represents a significant yet often overlooked public health issue affecting up to 90% of adolescent females globally. Its impact extends beyond physical discomfort to include academic absenteeism, diminished psychosocial well-being, and reduced quality of life. In resource-limited settings like Nepal, where menstrual health is shrouded in socio-cultural taboos, understanding adolescents’ knowledge and self-care practices is crucial for developing effective interventions. Objective: This study aimed to assess the level of knowledge and self-care practices regarding dysmenorrhea among female adolescent students in a non-medical college in Kathmandu, Nepal. Methodology: A descriptive cross-sectional study was conducted among 106 female students (Grades XI and XII) at Triton International College, selected via total enumeration and non-probability purposive sampling. Data were collected using a pre-tested, structured, self-administered questionnaire with four sections: socio-demographics, menstrual history, knowledge assessment (16 items), and practice assessment (9 items). Knowledge scores were categorized as Satisfactory (≥50%) or Unsatisfactory (<50%). Data analysis employed SPSS version 22, using descriptive statistics (frequencies, percentages, mean, SD) and inferential statistics (Chi-square test) to examine associations. Results: The mean age of participants was 16.2 years (±0.98). Dysmenorrhea prevalence was 85.8%. While 68.8% of students demonstrated a satisfactory level of knowledge, none achieved a "good" knowledge score. Primary information sources were mass media and relatives (100% each). Mefenamic acid was the most recognized (89.6%) and used (65.1%) pharmacological agent. The most common non-pharmacological practice was using a hot water bag (85.8%). A significant majority (85.8%) avoided physical activities during menstruation, and 84.9% reported a decrease in academic performance. No statistically significant associations were found between knowledge level and socio-demographic variables like age, ethnicity, or family type (p > 0.05). Conclusion: Findings indicate a high burden of dysmenorrhea coupled with moderate knowledge and limited, often suboptimal, self-care practices among adolescent students. There is a critical need for structured, school-based educational programs to disseminate evidence-based information, promote a wider repertoire of effective non-pharmacological strategies, and destigmatize menstrual health discussions. Future research should employ longitudinal and mixed-method designs to explore causal relationships and contextual barriers.